SPORTS AND TOURISM: TWO IMPORTANT PARTS OF A HEALTHY LIFE (International journal of artificial intelligence, 2025)
This article will talk about the importance of sports and tourism in society, their role in the formation of a healthy lifestyle, as well as the development of sports tourism. The article examines the interrelationships of sport and Tourism, its impact on physical and spiritual health, and its economic aspects. This topic has been analyzed as an important factor for wellness and cultural exchange in modern life.